Human tumor viruses: induction of three-dimensional alterations in the host genome structure - Minarovits, Janos (Frontiers in Microbiology, 2023)
Tumor viruses or oncoviruses change the gene expression pattern of their target cells in tissue culture, resulting in uncontrolled proliferation as well as a change in the social behavior of the infected cells: the oncovirus-transformed, immortalized cells are capable to form malignant neoplasms in suitable animal models. At present, seven human viruses are categorized as causative agents of distinct human malignancies. Recently, application of chromatin conformation capture technologies and three-dimensional (3D) molecular imaging techniques revealed that human tumor virus genomes interact with and induce alterations in the 3D host genome structure, which may contribute to oncogenesis.. This Mini Review aims to cover selected aspects of these new developments. Several papers, discussed briefly,describe how insertion of a novel, viral binding site for the 3D-genome organizer cellular protein, CCCTC-binding factor (CTCF), into theThis is a provisional file, not the final typeset article lymphomagenesis, It was also observed that chromatin contacts and super-enhancers, formed at integration sites of human papillomavirus genomes may facilitate cervical carcinogenesis.Recent results regarding the interactions of cellular genomes with the episomal, chromatinized DNA genomes of the oncogenic human herpesvirus, Epstein-Barr virus (EBV). will also be summarized., similarly to available data regarding contacts formed by episomal or integrated hepatitis B virus (HBV) DNA with host chromatin. Finally, a putative mechanism of hepatitis C virus (HCV) induced chromatin alterations will be presented, which may solve the riddle, how a cytoplasmic RNA virus without a viral oncogene could induce malignant transfrormation of hepatocytes.